Hierarchical Nanostructured Copper by Dealloying MnCu Alloy Ribbon for High-Performance Glucose Sensing - Jinyi Wang; Bowen Fan; Jiana Song; Chen Chen; Yuan Ji; Jincheng Yu (Crystals)
Electrochemical glucose sensing is vital for biomedical applications, particularly in diabetes management and continuous health monitoring. Among electrochemical sensors, non-enzyme-based sensors offer advantages such as cost-effectiveness, robust anti-interference capabilities, and environmental stability compared to enzyme-based ones. This study focuses on the development of non-enzyme-based glucose sensors utilizing hierarchical nanostructured copper (Cu) electrodes. The electrodes are fabricated by selectively dissolving components from an alloy precursor. Specifically, MnCu alloy ribbons prepared by melt rolling were used due to their favorable properties, and electrochemical dealloying was employed to create nanostructured Cu with high electrocatalytic activity for glucose oxidation. Three-dimensional bicontinuous nanoporous copper with an average pore size of 34 nm~86 nm and an average ligament size range of 45 nm~125 nm can be obtained. The optimized hierarchical nanostructured Cu electrodes exhibited excellent performance, including high sensitivity (0.652 mA·mM−1·cm−2), a wide linear detection range (0.001 mM to 1.5 mM), a low detection limit (0.73 μM), and a rapid response time. This work demonstrates the potential of nanostructured Cu in the advancement of non-enzyme-based glucose sensors.